Rambatan balik : Satu alternatif terhadap pengkelasan keberuntungan syarikat - Ismail, Noriszura; Jaaman, Saiful Hafizah; Shamsuddin, Siti Mariyam; Majid, Noriza (Universiti Utara Malaysia, 1999)
This paper aims to forecast and diflerentiate companies that are either making a profit or incurring a loss using the multiple linear regression method. Ratios to determine profitability of a company are used as data on 100 companies listed in the Kuala Lumpur Stock Exchange. A comparison will be made using a back-propagation model and multiple linear regression method.